If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12c + -10c + 10 = 12 Reorder the terms: 10 + 12c + -10c = 12 Combine like terms: 12c + -10c = 2c 10 + 2c = 12 Solving 10 + 2c = 12 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 2c = 12 + -10 Combine like terms: 10 + -10 = 0 0 + 2c = 12 + -10 2c = 12 + -10 Combine like terms: 12 + -10 = 2 2c = 2 Divide each side by '2'. c = 1 Simplifying c = 1
| (x)+(198-x)=198 | | (x+1)+(x+3)=198 | | h(t)=14+32x-16 | | 4.28(x-2)-2=-5 | | x-.10x=306 | | 3ln(3)-3ln(1)= | | 4x-7(35-10x)=-23 | | 5y^2+32y+40= | | (2x+1)*(10-3x)=0 | | -5y^2-32y-40= | | h=-4.9t^2+14t+2.5 | | 5x-16-x=2x+6x | | 5a^4+12a^3+4a^2=0 | | 9f(4f)= | | x+4x-6= | | .12x=y-110 | | 12x=y-110 | | 4x+25=y | | 2(8x-2)=12x+24 | | 4x+4-40=0 | | -2u^2+15u+25= | | .073x+0.34=9.1 | | .12x=y-105 | | y=(x*0.1)+(x*0.02)+5+100 | | 2x^5+3x^4-x^3+x^2-12= | | 7x^3-1-15x^3-4x^2+x-3= | | 3x+5=2x+6-4 | | -0.12q^2+1.8q-6=0 | | 33x+180=15 | | h(t)=-16t^2+800(t)+125 | | 4(v+5)=-2(9v-2)+8v | | 4x-(6x-2)=32 |